TOURISM INDUSTRY BANKRUPTCY ANALYSIS OF IMPACT COVID-19 PANDEMIC - Rieska Maharani; Tyasha Ayu Melynda Sari (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
This study aims to determine the bankruptcy analysis used in tourism industry companies due to the impact of Covid-19 in Indonesia. This study uses four bankruptcy analyzes, namely Springate (S-Score), Zmijewski analysis (X-Score), Grover analysis (G-Score), and Altman analysis (Z-Score). The sample used is a restaurant, hotel, and tourism company listed on the IDX during 2018-2020. The sampling technique was purposive sampling with a total sample of 27 companies. The results showed that the analysis, namely Springate (S-Score) there were 25 companies in a state of bankruptcy and two companies in good health, Zmijewski analysis (X-Score) there were four companies in bankruptcy and 23 companies in good health, Grover analysis (G-Score) Score) there are 14 companies in bankruptcy and 13 companies in good health, and Altman analysis (Z-Score) there are 18 companies in a state of bankruptcy, five companies in a state of a gray area (gray), and four companies in a state not bankrupt. The occurrence of Covid-19 in Indonesia also has an impact on tourism and its supporting sectors such as restaurants and hotels. The reason is the policies that have been set by the government to suppress the growth of Covid-19.